Estratégias de diversificação desenvolvidas por meio da agroindústria nas pequenas propriedades rurais - Sobczuk, Daiane Aline Tomaz (2022)
Rural property development cannot be based solely on traditional agricultural activities, which are constantly subjected to external shocks and economic trends. It is necessary to diversify the products and services that generate the livelihood of rural families. Thus, the general objective of this research is to analyze the process of implementing strategies for diversifying the livelihood of families of small rural producers in the municipality of Medianeira-PR. The research was carried out through a qualitative, descriptive and exploratory case study, based on structured interviews carried out between January and April 2022. The field of study is family properties that diversify their production through of family agroindustry, and the actors surveyed are their managers and the IDR extensionist. As the main findings of the research, it was identified that, in the implementation of the rural livelihood diversification strategy, the motivation is around income generation, permanence in rural areas and the opportunity to have a better quality of life, which is made possible from the access that properties have to the capital used in the process. Producers also strategically seek to add new knowledge to family traditions in order to create new products and services that are reversed through customer satisfaction. Investments in small innovations and the predominance of family labor are relevant aspects for the implementation of strategies in small rural properties. Finally, the performance of the income diversification strategy through agro-industry shows that access to natural, human, social, physical and financial capital is fundamental for the development of small family agro industries, in addition to the knowledge acquired by families the diversified business and the diversification strategy promote the livelihood and, consequently, the permanence of families and their successors on rural properties.